2006
DOI: 10.2174/157018006775240962
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Evaluation of Anthelmintic and Cytotoxic Properties of Bis- 1,3-Azole Analogs of Natural Products

Abstract: Tandem cyclizations to [2,5'] bis-1,3-azoles provided simplified and stable models of biological active marine natural products. The cytotoxic activity in HCT-15 cells and the effect on the L 4 larvae of Nippostrongylus brasiliensis of the heterocycles were evaluated and provided data that serve for the preparation of bioselective new therapeutic agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 1 publication
(1 reference statement)
0
5
0
Order By: Relevance
“…Bengazole and mycothiazole analogues, such as compounds 11 and 12 , were reported by Manta et al [29,30] These derivatives were found to have in vitro Nippostrongylus brasiliensis activity similar to bengazole and mycothiazole whilst being more chemically stable than the parent analogues. …”
Section: Recent Patent Landscape: New Antiparasitic Compoundsmentioning
confidence: 95%
“…Bengazole and mycothiazole analogues, such as compounds 11 and 12 , were reported by Manta et al [29,30] These derivatives were found to have in vitro Nippostrongylus brasiliensis activity similar to bengazole and mycothiazole whilst being more chemically stable than the parent analogues. …”
Section: Recent Patent Landscape: New Antiparasitic Compoundsmentioning
confidence: 95%
“…38,39 Furthermore, some thioformamides show antifungal 40 and antibacterial activity, 41 and they have been employed in the synthesis of thiazoles via the Hantzsch protocol. 42 We envisaged the use of Nurethane-protected amino alkyl thioformamides for the synthesis of the corresponding isonitriles through a dehydrosulfurization reaction.…”
Section: Methodsmentioning
confidence: 99%
“…Sulfur-containing compounds such as thioamides and thioesters have been found to be better reactants in the preparation of several heterocycle-tethered peptidomimetics and other related compounds compared to their oxygenated analogues. 38,39 Furthermore, some thioformamides show antifungal 40 and antibacterial activity, 41 and they have been employed in the synthesis of thiazoles via the Hantzsch protocol. 42 We envisaged the use of Nurethane-protected amino alkyl thioformamides for the synthesis of the corresponding isonitriles through a dehydrosulfurization reaction.…”
Section: Methodsmentioning
confidence: 99%
“…Molecules having pyrimidine as a core unit exhibit various biological activities such as antiviral , antibacterial , antitumor , anti‐inflammatory , and antifungal . Oxazoles are well‐known common motifs in natural products including phenoxan , noricumazoles , hennoxazoles , and leiodolides A and B , and many of them possess significant antimicrobial , cytotoxic , and anthelmintic activities. Thiazole derivatives are important components in medicinal chemistry because of their broad applications in drug development as antiviral , anticancer , antibacterial , antifungal , and anti‐inflammatory agents.…”
Section: Introductionmentioning
confidence: 99%